Dendrogenin A drives LXR to trigger lethal autophagy in cancers. Issue 1 (December 2017) - Segala, Gregory; David, Marion; de Medina, Philippe; Poirot, Mathias; Serhan, Nizar; Vergez, François; Mougel, Aurelie; Saland, Estelle; Carayon, Kevin; Leignadier, Julie; Caron, Nicolas; Voisin, Maud; et al.
Abstract Dendrogenin A (DDA) is a newly discovered cholesterol metabolite with tumor suppressor properties. Here, we explored its efficacy and mechanism of cell death in melanoma and acute myeloid leukemia (AML). We found that DDA induced lethal autophagy in vitro and in vivo, including primary AML patient samples, independently of melanoma Braf status or AML molecular and cytogenetic classifications. DDA is a partial agonist on liver-X-receptor (LXR) increasing Nur77, Nor1, and LC3 expression leading to autolysosome formation. Moreover, DDA inhibited the cholesterol biosynthesizing enzyme 3β-hydroxysterol-Δ8, 7 -isomerase (D8D7I) leading to sterol accumulation and cooperating in autophagy induction. This mechanism of death was not observed with other LXR ligands or D8D7I inhibitors establishing DDA selectivity. The potent anti-tumor activity of DDA, its original mechanism of action and its low toxicity support its clinical evaluation. More generally, this study reveals that DDA can direct control a nuclear receptor to trigger lethal autophagy in cancers. Dendrogenin A, cholesterol metabolite, has tumor suppressive properties but the mechanisms are unknown. Here the authors show that Dendrogenin A can induce autophagy-mediated cell death in both melanoma and acute myeloid leukaemia.